Improvement Studies on Manufacturing Operation Design for Mint Pilot Plant - Darmawan, Rosli (2002)
The difficulty faced by MINT's researchers during the transformation process from laboratory scale plant to pilot scale plant was investigated Analysis was carried out on the methodology used, plant development stages and the plant characteristics in order to identify the problem areas and weaknesses. Improvement effort on the pilot plant design methodology, based on Manufacturing System design techniques was carried out. The effectiveness of the improvement on the design methodology was analysed by comparing the plants' design parameters resulted from the existing methodology with that of the proposed methodology. Further evaluation on the plants operational performance was conducted through the plant operational simulation. Both plants were modelled using a discrete-event simulation software. The model was validated by comparing the results of the simulation with the actual operational data of the existing plant. Comparison from the design parameters and plant operational performance indicated that the proposed new plant performed better than the existing plant. The proposed plant has higher plant capacity; requires less floor area, capital cost and running cost; better machine, space and labour utilisation; less throughput time and less production lead time. This result is a manifestation of the plant design, which indicates that the proposed plant was designed better than the existing plant. Thus, with this proposed design methodology, MINT's researchers will be able to design a better pilot plant and enable them to continue further with their research activities.